Analisis Faktor Kepemimpinan terhadap Pelanggaran HAM Studi Kasus: Enforced Disappearance di Mesir oleh Rezim Abdel Fattah al-Sisi - Rizki Ananda; Hermini Susiatiningsih (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
The enforced disappearance in Egypt occurred in 2013 after the military coup by Abdel Fattah al-Sisi against the previous President, Muhammad Mursi. Coercive actions were taken by the state to protect state security including acts of enforced disappearance. The data shows that there have been 1176 cases of enforced disappearances from 2013 to 2017. However, Egypt is a democratic country by regulationand also recognizes individual freedom in the constitution. This research aims to determine how the influence of the leadership factors of President Abdel Fattah al-Sisi on enforced disappearance cases in Egypt. For analyzing the influence of leadership factors, this research use Behavioral theory with qualitative method and descriptive research by using literature review. The result will explain how the leadership of Abdel Fattah al-Sisi is formed and can influence enforced disappearance cases in Egypt.